ON DISTINGUISHED POLYNOMIALS AND THEIR PROJECTIONS - Caliskan, Erhan; Rueda, Pilar (SUOMALAINEN TIEDEAKATEMIA, 2012)
We study projections and injections between projective tensor products spaces or spaces of polynomials and we show that the example of a polynomial constructed in [4], that is neither p-dominated nor compact, can be identified with the projection map of the symmetric tensor product onto the space. Also we give a characterization of the weak and quasi approximation properties on symmetric tensor products.
Keywords: Projective tensor product; dominated polynomial; approximation property; QUASI APPROXIMATION PROPERTIES; BANACH-SPACES; HOLOMORPHIC MAPPINGS; WEAK; COMPACT; Mathematics